Scepticism as a moderator of Generation Z’s attitudes towards CSR and green products - Skowron-Mielnik, Beata; Borusiak, Barbara; Cyfert, Szymon; Stefańska, Magdalena; Szymkowiak, Andrzej; Waligóra, Anna (Economics and Environment, 2025)
The aim of the study is to explain how Generation Z students' scepticism towards environmental claims moderates the relationship between the value of green consumption and attitudes towards corporate social responsibility (CSR) and green products. Data collected through a computer-assisted web interview survey from 582 students of economics and business were analysed through structural equation modelling. The results suggest that green consumption values are positively related to attitudes towards CSR and green products. They also show that scepticism about environmental claims plays an important role in moderating the relationship between green consumption values and attitudes towards green products, but has no effect on the relationship between green consumption values and students' attitudes towards CSR. The model is limited to only a few dimensions, but it would be cognitively interesting to see how perceptions of greenwashing influence attitudes towards green products. The limitations of the study are also due to the sample used to test the hypotheses and the conceptual model. The results may be useful for the design of business marketing communications and educational programmes. In the future, we suggest identifying how to transform limited trust in green products, which is an inhibiting factor, into an incentive to develop positive attitudes towards green product claims.